2002
DOI: 10.1002/1521-396x(200205)191:1<89::aid-pssa89>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Heat Treatment and Grain Size on the Damping Capacity of an Fe-Cr-Al Alloy

Abstract: The effect of heat treatment and grain size on the damping capacity of an Fe-Cr-Al alloy with composition of (wt%) Fe-25Cr-5Al has been investigated. It has been shown that annealing temperature and grain size have a significant influence on the damping capacity and strain amplitude dependence of the alloy. Moderate annealing and grain size are necessary for a higher damping capacity, although if annealing does not yield relatively large grains, it has little effect on the damping capacity. The alloy has a rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…29 Briefly, the coarse grain size in pure Ni, with less grain boundaries and dislocation density, facilitates a rapid and large internal energy dissipation through sliding, thus results in high damping capacity and declined amplitude. 30 After the fluctuations at the beginning, both of the resonant frequency and scanning angle changed slightly, which suggests the plastic deformation within Ni beam reaches to a stable region.…”
Section: Micromechanical Property Measurement Of G−ni Compositementioning
confidence: 99%
“…29 Briefly, the coarse grain size in pure Ni, with less grain boundaries and dislocation density, facilitates a rapid and large internal energy dissipation through sliding, thus results in high damping capacity and declined amplitude. 30 After the fluctuations at the beginning, both of the resonant frequency and scanning angle changed slightly, which suggests the plastic deformation within Ni beam reaches to a stable region.…”
Section: Micromechanical Property Measurement Of G−ni Compositementioning
confidence: 99%
“…[5][6][7][8][9][10][11] Since the Q -1 of Fe-23.0Al-6.0Ni alloys shows low values under magnetic field, the magneto-mechanical damping seems to appear. It is also noted that the λm of the alloys showed higher values compared with Fe-23.0Al binary alloys as shown in Fig.…”
Section: High Damping Capacity In Fe-al-ni Alloysmentioning
confidence: 99%
“…At low strain amplitudes and ambient temperature, the high damping capacity of Fe-Al alloys is usually attributed to the magneto-mechanical damping associated with the irreversible motion of magnetic domain walls. [5][6][7][8][9][10][11][12] However, the ultimate tensile strength of binary Fe-Al alloys was approximately 500 MPa, not enough to use the alloys to the automobile vibration sources.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hysteretic damping with magneto-mechanical origin in Fe-Al based alloys was examined to develop these alloys as high damping materials. [6][7][8][9][10][11] As a result, the alloys have been successfully developed as high damping alloys in Japan. 6,7) It was strongly suggested that the high damping capacity of Fe-Al based alloys at low strain amplitude and at ambient temperature was caused by an irreversible movement of magnetic domain walls during cyclic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) It was strongly suggested that the high damping capacity of Fe-Al based alloys at low strain amplitude and at ambient temperature was caused by an irreversible movement of magnetic domain walls during cyclic deformation. [5][6][7][8][9] In the present study, the origin of high Q…”
Section: Introductionmentioning
confidence: 99%